Neuraxial Anesthesia in Parturients With Low Platelet Counts. Issue 6 (December 2016) - Bernstein, Jeffrey; Hua, Betty; Kahana, Madelyn; Shaparin, Naum; Yu, Simon; Davila-Velazquez, Juan
Abstract : (Abstracted from Anesth Analg, 123:165–167, 2016) Clinicians who perform obstetric anesthesia must consider the risk of spinal-epidural hematoma in patients with thrombocytopenia when deciding whether to administer neuraxial anesthesia. Unfortunately, however, there is a paucity of data studying this potential complication that might assist in decision making.